Assessment of Workplace Discrimination against Individuals with Autism Spectrum Disorder (ASD) - Ashley-Ann Cooper; Bahaudin G. Mujtaba (SocioEconomic Challenges)
Autism, also known as autism spectrum disorder (ASD), is a genetic / neurological condition, impacting about 2% of young children in the United States, which causes certain challenges in one’s communication, learning, socialization, and even stress management coping skills. Children with autism tend to demonstrate the presence of constrained, confined, or repetitive patterns of behaviors, activities, and interests. People with ASD learn differently than others, and their attention can be gained and maintained through repetition and routine. Individuals who have a mild or extreme form of ASD often experience more difficulty adjusting to changes in the work environment and society in general. Consequently, even though many individuals with ASD can perform their jobs successfully, they are often discriminated against and not afforded reasonable accommodations for them to gain and maintain steady employment. In this paper, we provide an overview of ASD to create awareness, along with recommendations so that more autistic adults can be employed in the workplace. Employers and manager should know that autism spectrum disorder involves a range of symptoms that cause difficulty communicating, such as flat affect (or diminished emotional expression), poor eye contact, and difficulty understanding nonverbal cues. These symptoms make it difficult to find and maintain employment, and people with autism regularly deal with discrimination and prejudice, both in and out of the workplace. Employers show less interest in hiring neurodivergent employees even if they are qualified and capable of performing the required work, and many do not provide sufficient accommodations to those that they do hire.